Nitrogen fertilizer equivalence of black soldier fly frass fertilizer and synchrony of nitrogen mineralization for maize production - Beesigamukama, D.; Mochoge, Benson; Korir, N.; Musyoka, M.W.; Fiaboe, K.; Nakimbugwe, D.; Khamis, F.M.; Subramanian, S.; Dubois, T.; Ekesi, S.; Tanga, C.M. (MDPI, 2020)
The use of black soldier fly frass fertilizer (BSFFF) is being promoted globally. However, information on nitrogen (N) fertilizer equivalence (NFE) value and synchrony of N mineralization for crop production remains largely unknown. Comparative studies between BSFFF and commercial organic fertilizer (SAFI) were undertaken under field conditions to determine synchrony of N release for maize uptake. The BSFFF, SAFI, and urea fertilizers were applied at the rates of 0, 30, 60, and 100 kg N ha−1. The yield data from urea treated plots were used to determine the NFE of both organic inputs. Results showed that maize from BSFFF treated plots had higher N uptake than that from SAFI treated plots. High N immobilization was observed throughout the active growth stages of maize grown in soil amended with BSFFF, whereas soil treated with SAFI achieved net N release at the silking stage. Up to three times higher negative N fluxes were observed in SAFI amended soils as compared with BSFFF treated plots at the tasseling stage. The BSFFF applied at 30 and 60 kg N ha−1 achieved significantly higher NFE than all SAFI treatments. Our findings revealed that BSFFF is a promising and sustainable alternative to SAFI or urea for enhanced maize production.